(untitled) (Journal of Economic Research & Business Administration, 2024)
This study aims to investigate the functional capabilities of the learning management system as an effective tool for quality management in technical and vocational education, allowing for the analysis of the current situation and assessment of the effectiveness of work at all levels. This study has significant theoretical and practical value for deepening and expanding the theory of quality assessment in technical and vocational education and the management system, as well as for the development of scientific, standardized and adaptive systems and models in the future. This study aims to highlight the significance of an integrated model of various information systems’ success in using LMS in technical and vocational education (TVE) institutions. The work also provides a comparative analysis of the features of using LMS in secondary and higher education institutions and TVE. Thus, this study identifies promising areas for further analysis and scientific research, providing valuable information on the use of LMS in the context of TVE. In addition, the study reveals new factors influencing the effectiveness of LMS in TVE institutions. Key words: technical and vocational education, quality management, learning management system.